Clinical workflow of sonographers performing fetal anomaly ultrasound scans: deep learning-based analysis - Drukker, L; Sharma, H; Karim, JN; Droste, R; Noble, J; Papageorghiou, AT (Wiley, 2022)
Objective: Despite decades of obstetric scanning, the study of sonographer workflow remains largely unexplored. In the second trimester for example, sonographers use scan guidelines to guide their acquisition of standard planes and structures; however, the scan acquisition order is not prescribed. Using deep learning-based video analysis, the aim of this study was to develop a deeper understanding of the clinical workflow sonographers undertake during second-trimester anomaly scans.